2010
DOI: 10.3233/jad-2010-100060
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E3 as a Risk Factor for Alzheimer's Disease Under Conditions of Nutritional Imbalance

Abstract: Abstract. The presence of one or more copies of the E4 allele of apolipoprotein E (ApoE) is strongly associated with of Alzheimer's disease (AD). The impact of E4 on neurodegeneration is potentiated by dietary oxidative challenge. Our prior studies in transgenic mice demonstrate that, in the face of dietary oxidative challenge, E3 does not provide any further protection than E4 or lack of murine ApoE for aggression, oxidative damage, presenilin-1 expression, and γ-secretase activity, and provides only partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Given the increasing evidence of oxidative damage or deficient myelination in psychiatric disorders, it is not surprising that several clinical trials of an antioxidant intervention have shown efficacy in several disorders. Nacetyl cysteine (NAC) supplementation is well tolerated and helps replenish the rate-limiting supply of cysteine for glutathione (a tripeptide that is arguably the principal brain antioxidant) (reviewed in 383) (249,384) and is decreased in the brain of psychiatric subjects (141). NAC penetrates the blood-brain-barrier (385) and has been shown to protect oligodendrocytes from oxidative damage and a variety of toxins (134,(386)(387)(388)(389)(390)(391).…”
Section: Myelotoxicity and Treatment Effectsmentioning
confidence: 99%
“…Given the increasing evidence of oxidative damage or deficient myelination in psychiatric disorders, it is not surprising that several clinical trials of an antioxidant intervention have shown efficacy in several disorders. Nacetyl cysteine (NAC) supplementation is well tolerated and helps replenish the rate-limiting supply of cysteine for glutathione (a tripeptide that is arguably the principal brain antioxidant) (reviewed in 383) (249,384) and is decreased in the brain of psychiatric subjects (141). NAC penetrates the blood-brain-barrier (385) and has been shown to protect oligodendrocytes from oxidative damage and a variety of toxins (134,(386)(387)(388)(389)(390)(391).…”
Section: Myelotoxicity and Treatment Effectsmentioning
confidence: 99%